A comparison of authoritative and participative leadership styles regarding physical education teachers' efficiency - Honari, Habib (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
The purpose of this study is to compare the authoritative and participative leadership styles regarding physical education teachers` efficiency. To this end, 40 school principals and 40 male and female physical education teachers at secondary schools were randomly assigned to participate in the study . School principals performance assessed with Fiddler leadership style questionnaire with reliability coefficient of 0.86 by teachers.Also, teachers`performance evaluated with teacher -made questionnaire with validity coefficient of 0.87 (Cronbach Alpha) completed by the students. Data distribution was normal shown in this study using kolmogorov-smirnov test. Additionally,statistical method in terms of statistical model is parametric,while non-parametric statistics is employed for heterogeneous groups through which desired hypotheses discussed using Pearson correlation test, Spearman correlation coefficient and T –test. Results indicate that there exists a significant relationship between the leadership style of school principals and physical education teachers efficiency at 5% significance level.The results show that participative leadership style would end up with substantial efficiency of male and female education teachers, whereas authoritative leadership style has shown the lowest efficiency.